STUDY THE EFFECT OF HYLOCEREUS POLYRHIZUS SOME ANTIOXIDANT FACTORS IN CHRONIC KIDNEY DISEASE PATIENTS - Azzawi, Mohammed Jumaah (PT. Antis International Publisher, 2024)
The current work was aimed to study the effect of Hylocereus polyrhizus some antioxidant factors in CKD patients and healthy persons. An overall total of (80) CKD patients were included in this study. The patients were between the ages of 20 and 60. Each patient's case information sheet was compiled with information on their name, age, sex, marital status, place of residence, history of chronic diseases, history of drug use, history of smoking, and type of operation. These patients were hospitalized to Kirkuk, Iraq's Kirkuk Teaching Hospital between April and July 2022. 50 healthy individuals served as the control group in this experiment. testing for a few biological elements. The analysis of the peel extract from H. polyrhizus revealed the presence of saponin, flavonoid, tannin, polyphenol, alkaloid, quinone, and terpenoid compounds. Total antioxidant capacity level in male and female were showed significant (P≤0.05) reduced in comparison to the heath group. After using dragon fruits extract, Total antioxidant capacity level were improved and there was non-significant (P≤0.05) changes in comparison to the heath group. Total oxidant status level in male and female were showed significant (P<0.05) elevated in comparison to the heath group. After using dragon fruits extract, Total oxidant status level (951.8±57.4) were improved and there was non-significant (P≤0.05) changes in comparison to the heath group. Based on the results of the current study, it was found that dragon fruits extract has an effective role as an antioxidant.